Mentoring Student Teachers for Teaching in Culturally Diverse Schools to Promote Inclusive Science Teaching - Lewis, Elizabeth; Hasseler, Elizabeth; Covil, Karen; Tankersley, Amy; Frack, Susan (Innovations in Science Teacher Education, 2025)
Educating highly qualified science teachers requires careful collaboration among teacher preparation programs, college or university supervisors, school partners, and especially effective cooperating secondary science teachers. Mentoring student teachers is a complex yet crucial part of the teacher preparation program. In this case study of a science teacher preparation program at a large four-year Great Plains university, we envisioned key aspects of strong mentoring of student teachers in science by cross-referencing a model of intersectional equity developed by the Advancing Coherent and Equitable Systems of Science Education project, the 2020 NSTA science teacher preparation standards, and Campbell and Brummett’s (2007) teacher coaching model. These documents have informed our teacher preparation program and interactions with our preservice teachers. One such decision has been to couple coursework promoting instructional strategies to support diverse learners with the strategic clinical placement of over 75% of our preservice teachers in high-need schools. These choices have yielded positive results. When we reviewed the 10-year employment history of our secondary science teacher alumni post-pandemic, 70-75% of undergraduate and master’s program alumni were still employed as science teachers. Approximately 70% of those teachers have been employed in high-need schools. In this article, we provide specific guidelines and a tool for effective mentorship of preservice science teachers. We hope that science teacher educator teams find this tool useful, clear, and practical to share with mentor teachers to empower them to implement these strategies with their student teachers to accelerate their journey toward inclusive science teaching.